Potential of Ionizing Radiation Application for Reducing Environmental Risks Related to Solids Residues - Sueli Ivone Borrely; Maria Veronica Vogt; Simone Aquino; Vanessa SG Garcia; Jose Pachado (Brazilian Journal of Radiation Sciences)
The enormous amount of solids residues and related cost for a suitable disposal have increased in megacities as São Paulo and Buenos Aires. Inovative technologies may be used in order to face managing progams with inovative techniques for for recycling or recover of materials. Gamma radiation was applied in laboratory scale for two different types of residues: fungi control in vehicular air filters, and for rat bedding waste (RBW) disinfection. Both materials may be used after irradiation and the radiation doses required will be discussed. Part of experiments carried out in Argentina evidenced the suitable use of vermicomposting for growing Calendula officinalis. Radiation doses from 10 kGy up to 30 kGy were tested for controlling microorganisms during the projects and were very effective. For filters disinfection experiments, DNA sequencing analysis for the fungi that survived after irradiation not only confirmed the presence of Penicillium, Fusarium and Aspergillus (toxigenic), fungi but also improved the data: the contamination included Aspergillus niger, Aspergillus flavus, Penicillium glabrum specie complex and Fusarium incarnatum-equiseti specie complex.